World Food Prices and Monetary Policy - Chang, Roberto (IMF Working Papers; Working Paper ;, 2010)
The large swings in world food prices in recent years renew interest in the question of how monetary policy in small open economies should react to such imported price shocks. We examine this issue in a canonical open economy setting with sticky prices and where food plays a distinctive role in utility. We show how world food price shocks affect natural output and other aggregates, and derive a second order approximation to welfare. Numerical calibrations show broad CPI targeting to be welfare-superior to alternative policy rules once the variance of food price shocks is sufficiently large as in real world data.